Mapping the Underground: Geotechnical Physical Properties Insights from Bengkulu City - Mase, Lindung Zalbuin; Kamal, Thomas Mustafa; Putri, Melly Zuhadjar; Misliniyati, Rena; Chaiyaput, Salisa (My University, 2026)
This study presents a three-dimensional engineering geology model of soil-layer physical parameters in Bengkulu City, Indonesia. The model provides an integrated understanding of the subsurface profile to support construction design and planning. Three-dimensional modelling is applied to identify subsurface geological layers and visualize key soil physical properties using colour-scaled parameter distributions. The analysed parameters include shear wave velocity, plasticity index, saturated unit weight, bulk unit weight, dry unit weight, water content, and degree of saturation. Data interpolation is performed using the Inverse Distance Weighting method, which is suitable for estimating parameter continuity within layers in 3D geological modelling. The resulting model identifies five generalised subsurface layers: sand, clay, soft rock, medium rock, and hard rock. Interpolated parameter variations are illustrated through geological profiles and Probability Density Function plots, enabling more straightforward interpretation of value distributions across the study area. Overall, the findings offer practical insights and essential baseline information for engineers and planners conducting soil investigations in Bengkulu City.
Keywords: Geological modelling; Geological variation; Inverse distance weighting; Physical properties